2023
DOI: 10.1177/15579883231207481
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pre-Exposure Prophylaxis Accessibility, Knowledge, Barriers, and Facilitators Among Men Who Have Sex With Men in Bulawayo, Zimbabwe

Perez Livias Moyo,
Wilfred Njabulo Nunu

Abstract: Great strides have been made globally toward ending HIV and AIDS as a threat by 2030, although the rate of new HIV infections among men who have sex with men remains very high. Due to their risk of getting HIV and AIDS, utilization of pre-exposure prophylaxis (PrEP) can potentially reduce the risk of HIV transmission among this population. This study sought to analyze the accessibility, knowledge, and potential barriers and facilitators to assessing PrEP by men who have sex with men. The quantitative method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…Having many MSM-friendly facilities means more MSM are going to access PrEP in a non-judgmental environment, offering differentiated and support services, hence improving PrEP use. The study findings concur with other literature sources that reported increasing the number of health care facilities and offering PrEP services as important facilitators ( Harawa et al, 2016 ; Moyo & Nunu, 2023a ). Other scholars reported support organizations or clubs for PrEP users as vital facilitators in improving PrEP utilization ( Graham et al, 2022 ; Harawa et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Having many MSM-friendly facilities means more MSM are going to access PrEP in a non-judgmental environment, offering differentiated and support services, hence improving PrEP use. The study findings concur with other literature sources that reported increasing the number of health care facilities and offering PrEP services as important facilitators ( Harawa et al, 2016 ; Moyo & Nunu, 2023a ). Other scholars reported support organizations or clubs for PrEP users as vital facilitators in improving PrEP utilization ( Graham et al, 2022 ; Harawa et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, health service providers in these facilities are trained to provide affirming sexual health services to gender and minority populations, thus ensuring a safe and friendly environment. These findings align with other authors who reported that having MSM-friendly facilities is important in the uptake and adherence of PrEP and having relatable health care providers is vital in ensuring improved PrEP uptake among this population ( Graham et al, 2022 ; Moyo & Nunu, 2023a ; Pichon et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%